2010
DOI: 10.1007/s11431-010-4100-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow structures in flat plate boundary layer induced by pulsed plasma actuator

Abstract: The flow field in the flat plate boundary layer induced by the pulsed plasma actuator was simulated by solving the Navier-Stokes equations with a phenomenological DBD plasma model. The effects of actuation strength, wave form and frequency on the flow structures induced by the unsteady pulsed plasma actuator were investigated. The results indicated that a series of vortex pairs were formed in the boundary layer, and decayed in downstream convection following the exponential law. The strength of vortex pair was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Khoshkhoo et al [16] explored the effects of body force over a NACA0015 airfoil with this model and found that dimensions, magnitude and the location of the body force all have significant impact on the separation control. Zhang et al [17] employed it to study the flow structures of the boundary layer in a flat plate induced by a plasma actuator. Yu et al [11] used the linear body approach and found that the vortex pairs, which are reduced by a plasma, would enhance the energy exchanged between the near wall region and the free stream.…”
Section: Introductionmentioning
confidence: 99%
“…Khoshkhoo et al [16] explored the effects of body force over a NACA0015 airfoil with this model and found that dimensions, magnitude and the location of the body force all have significant impact on the separation control. Zhang et al [17] employed it to study the flow structures of the boundary layer in a flat plate induced by a plasma actuator. Yu et al [11] used the linear body approach and found that the vortex pairs, which are reduced by a plasma, would enhance the energy exchanged between the near wall region and the free stream.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its simple construction, convenient installation and fast time response, the plasma actuator has attracted much attention in aeronautical applications. [1][2][3][4][5][6][7][8][9][10][11][12][13] Typical asymmetrical DBD plasma actuators include an exposed and covered electrode separated by a thin insulating material, with the covered electrode encapsulated by the dielectric material and the exposed electrode exposed to the air, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…They are simple to implement and computationally cheap. Therefore, they are used in different applications [20,21].…”
Section: Introductionmentioning
confidence: 99%